2008
DOI: 10.1107/s0108767308016826
|View full text |Cite
|
Sign up to set email alerts
|

Stacking and twin faults in close-packed crystal structures: exact description of random faulting statistics for the full range of faulting probabilities

Abstract: The classical model of independent random single deformation faults and twin faulting in face-centered-cubic and hexagonal close packing is revisited. The model is extended to account for the whole range of faulting probabilities. The faulting process resulting in the final stacking sequences is described by several equivalent computational models. The probability sequence tree is established. Random faulting is described as a finite-state automaton machine. An expression giving the percent of hexagonality fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…and 2H CPSs: the RGDF process Estevez- Rams et al (2008) recently showed that simultaneous random growth and deformation stacking faults (SFs) in 2H and 3C CPSs can be modeled for all values of the fault parameters by a simple HMM, and this is shown in Fig. 8.…”
Section: Random Growth and Deformation Faults In Layered 3cmentioning
confidence: 99%
See 4 more Smart Citations
“…and 2H CPSs: the RGDF process Estevez- Rams et al (2008) recently showed that simultaneous random growth and deformation stacking faults (SFs) in 2H and 3C CPSs can be modeled for all values of the fault parameters by a simple HMM, and this is shown in Fig. 8.…”
Section: Random Growth and Deformation Faults In Layered 3cmentioning
confidence: 99%
“…Warren (1969) uses P 0 m ; P þ m and P À m ; Kabra & Pandey (1988) call these PðmÞ; QðmÞ and RðmÞ; and Estevez- Rams et al (2008) use P 0 ðÁÞ; P f ðÁÞ and P b ðÁÞ. Since we prefer to reserve the symbol 'P' for other probabilities previously established in the literature, here and elsewhere we follow the notation of Yi & Canright (1996), with a slight modification of replacing 'Q r ðnÞ' with 'Q a ðnÞ'.…”
Section: Correlation Functions 425mentioning
confidence: 99%
See 3 more Smart Citations